2012
DOI: 10.1098/rspb.2012.0813
|View full text |Cite
|
Sign up to set email alerts
|

Genomic consequences of multiple speciation processes in a stick insect

Abstract: Diverse geographical modes and mechanisms of speciation are known, and individual speciation genes have now been identified. Despite this progress, genome-wide outcomes of different evolutionary processes during speciation are less understood. Here, we integrate ecological and spatial information, mating trials, transplantation data and analysis of 86 130 single nucleotide polymorphisms (SNPs) in eight populations (28 pairwise comparisons) of Timema cristinae stick insects to test the effects of different fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
153
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(157 citation statements)
references
References 41 publications
(63 reference statements)
4
153
0
Order By: Relevance
“…1B) form host races on two sympatric rosid host species. Pairs of host-associated populations form repeatedly across the landscape, and populations cluster phylogenetically by geography rather than by host plant; this scenario is indicative of repeated parallel divergence (Nosil et al 2012; Soria-Carrasco et al 2014). …”
Section: Divergence Of Host-associated Populations and Racesmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) form host races on two sympatric rosid host species. Pairs of host-associated populations form repeatedly across the landscape, and populations cluster phylogenetically by geography rather than by host plant; this scenario is indicative of repeated parallel divergence (Nosil et al 2012; Soria-Carrasco et al 2014). …”
Section: Divergence Of Host-associated Populations and Racesmentioning
confidence: 99%
“…1C; Egan et al 2015), predation in Timema (Fig. 1D; Nosil et al 2012), and host plant nutritional and defensive properties in Acyrthosiphon (Hawthorn and Via 2001). …”
Section: Divergence Of Host-associated Populations and Racesmentioning
confidence: 99%
“…Some loci are likely to be shared between incipient species, while selection maintains divergence at others (Turner et al 2005;Nosil et al 2009). Recently, considerable progress has been made in documenting patterns of genomic divergence between incipient species (Hohenlohe et al 2010;Lawniczak et al 2010;Michel et al 2010;Ellegren et al 2012;Nosil et al 2012;Gagnaire et al 2013). Genome-wide studies of threespine sticklebacks (Hohenlohe et al 2010(Hohenlohe et al , 2012 and Ficedula flycatchers (Ellegren et al 2012) revealed patterns of divergence consistent with a model of ''islands'' of divergence amidst a sea of gene flow.…”
mentioning
confidence: 93%
“…This is partly because it is challenging to reconstruct ancestral ranges and therefore almost impossible to know for sure the extent of historical contact between species. Fortunately, genomic approaches are now beginning to allow us to address these long-standing questions from a different angle, by documenting the extent of admixture between species on a genome-wide scale (Kulathinal et al 2009;Ellegren et al 2012;Garrigan et al 2012; The Heliconius Genome Consortium 2012; Nosil et al 2012). Speciation genomics therefore offers an opportunity to address long-standing questions regarding the extent to which divergence and speciation occurs in the face of ongoing gene flow.…”
mentioning
confidence: 99%
See 1 more Smart Citation